2020
DOI: 10.1038/s41366-020-00708-y
|View full text |Cite
|
Sign up to set email alerts
|

Examining differences between overweight women and men in 12-month weight loss study comparing healthy low-carbohydrate vs. low-fat diets

Abstract: Background/objectives Biological sex factors and sociocultural gender norms affect the physiology and behavior of weight loss. However, most diet intervention studies do not report outcomes by sex, thereby impeding reproducibility. The objectives of this study were to compare 12-month changes in body weight and composition in groups defined by diet and sex, and adherence to a healthy low carbohydrate (HLC) vs. healthy low fat (HLF) diet. Participants/methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
4
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
2
17
4
3
Order By: Relevance
“…In our cohort, females were more likely than men to achieve remission. This finding is consistent with previous studies and may be due to greater motivation in females to lose weight as a result of greater dissatisfaction with weight, stronger preference for lower fat diet, and societal pressure for them to be slim 17,18 . Older people and those with fewer comorbidities were also more likely to achieve remission.…”
Section: Discussionsupporting
confidence: 91%
“…In our cohort, females were more likely than men to achieve remission. This finding is consistent with previous studies and may be due to greater motivation in females to lose weight as a result of greater dissatisfaction with weight, stronger preference for lower fat diet, and societal pressure for them to be slim 17,18 . Older people and those with fewer comorbidities were also more likely to achieve remission.…”
Section: Discussionsupporting
confidence: 91%
“…Strong adherence level is associated with successful outcomes in weight management [ 61 ]. A recent study investigating sociocultural gender factors which influence food behaviours, such as dietary preferences and adherence, reported that men were more adherent to a healthy low-carbohydrate (HLC) than women ( p = 0.02) vs. healthy low-fat (HLF) diet [ 62 ]. Another possible reason for this may be the addition of regular one-to-one support provided by the researcher, where goal setting and self-monitoring of food intake were encouraged using motivational interviewing techniques and behavioural change skills.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary analysis of data for biological sex differences in weight variation within the mRMR and eRMR groups, or other sex-related factors, such as genotype, hormones, metabolic syndrome, or psychosocial factors that may affect either adherence to dietary intervention or weight reduction response were not investigated. Aronica et al [ 62 ] highlighted the need for such analysis while acknowledging that a limited amount of weight reduction studies demonstrated sufficient power to compare the effects of energy restriction diets on weight outcomes in women vs. men. The present study duration was 12 weeks, thus it is unknown whether participants in the mRMR or eRMR groups maintained weight reduction over a longer period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neben Präventionsmaßnahmen existieren verschiedene konservative und bariatrische Therapieoptionen, die in den S3-Leitlinien "Prävention und Therapie der Adipositas" und "Chirurgie der Adipositas und metabolischer Erkrankungen" dargelegt werden [7,10]. Basierend auf den Empfehlungen der S3-Leitlinie "Chirurgie der Adipositas und metabolischer Erkrankungen" stellt die tiven Adipositastherapie hinweisen, deren zugrunde liegende Mechanismen nicht ausreichend verstanden sind [19,20]. Die oben zitierten Studien zeigen eindrucksvoll, dass weniger die Gewichtsreduktion, sondern vielmehr die langfristige Stabilisierung ein wichtiges Problem insbesondere der nichtchirurgischen Adipositastherapie darstellt.…”
Section: Diskussionunclassified